Challenges for Social Work Training: Field Professionals’ Experiences in Internship Supervision to the south of Chile - Sanhueza-Díaz, Lilian Olimpia; Álvarez-Caro, Carolina Andrea; Sanhueza-Jara, Sergio Rodrigo; Vargas-Gallardo, Karina Monserrat (Prospectiva. Revista de Trabajo Social e Intervención Social, 2025)
The article analyzes the experience of field professionals supervising internships of Social Work students at the Catholic University of Chile. Based on a Teaching Innovation Project (PID) consisting of a training program on supervision in Social Work, it delved into a) the central main tensions facing Social Work in Chile were discussed in detail, b) the strengths and weaknesses of professional vocational training from the experience of institutional supervision, and c) the role of supervision and the professional in charge of this process. Using qualitative methodology, the participants' course narratives report of the participants in the course were transcribed, categorized, and interpreted using qualitative content analysis technique. The results highlight show that professionals' concerns are concerned about the effects of neoliberalism on public policies, the practice of the profession, and professional training, as well as the need to recognize contexts of inequality and social exclusion by valuing sociocultural diversity in which the profession develops it task. Among the strengths of vocational training, proactivity and willingness are mentioned, while among the weaknesses are difficulties in theoretical argumentation, critical analysis and the use of information technologies. The commitment to the supervision process stands out, as Regarding supervision, they conceive it as a space for “reflective reflexive discussion”, based on accompaniment, feedback, and critical reflection on reality, to generate pertinent action proposals. This aligns with the literature regarding the internship supervisor as a “practical educator”.